Taxonomy and bioacoustics of scaly crickets (Orthoptera, Mogoplistidae, Mogoplistinae) from Borneo and Singapore - Tan, Ming Kai; Japir, Razy; Chung, Arthur Y.c.; Wahab, Rodzay Bin Haji Abdul; Robillard, Tony (Zootaxa, 2022)
A species of scaly cricket is described here: Ornebius lupus sp. nov. from the mangrove forests in Singapore. Ornebius pullus Ingrisch, 2006 is recorded in eastern Sabah for the first time. The calling songs of Cycloptiloides bimaculatus Tan et al., 2021 and Ornebius pullus from Sabah are described. We also revise the diagnosis of Ectatoderus nigrofasciatus Tan et al., 2021 from Brunei Darussalam.